2013
DOI: 10.1002/chem.201302170
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efficacy and Broadening of Antibacterial Action of Drugs via the Use of Capped Mesoporous Nanoparticles

Abstract: Bug busters: A novel nanodevice consisting of mesoporous nanoparticles loaded with vancomycin and capped with ε-poly-L-lysine (ε-PL) was prepared and its interaction with different Gram-negative bacteria studied. A remarkable improvement in the efficacy of the antimicrobial drug ε-PL and a broadening of the antimicrobial spectrum of vancomycin is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
(66 reference statements)
1
34
0
1
Order By: Relevance
“…The error bars present the SEM of at least two independent experiments in duplicate. bacteria, effort is also being directed toward the improving pharmacological properties, potency and delivery of known antibiotics, 19 , 45 , 27 , 46 , 20 Here we employed a recently described nanotechnology approach, 27 to enhance permeability of recently identified putative histidine kinase autophosphorylation inhibitors (HKAIs) in Gr− bacteria and demonstrated that they are bactericidal for Gr− bacteria. 12 The previously reported HKAIs were bactericidal for Gr + bacteria but not Gr− bacteria despite the fact they inhibit the autophosphorylation of HKs from both Gr− and Gr + in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The error bars present the SEM of at least two independent experiments in duplicate. bacteria, effort is also being directed toward the improving pharmacological properties, potency and delivery of known antibiotics, 19 , 45 , 27 , 46 , 20 Here we employed a recently described nanotechnology approach, 27 to enhance permeability of recently identified putative histidine kinase autophosphorylation inhibitors (HKAIs) in Gr− bacteria and demonstrated that they are bactericidal for Gr− bacteria. 12 The previously reported HKAIs were bactericidal for Gr + bacteria but not Gr− bacteria despite the fact they inhibit the autophosphorylation of HKs from both Gr− and Gr + in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…27 Figure 2 shows a schematic representation of the expected mechanism of action of N. Rho and N.HKAIs solids in the presence of Gr− bacteria. Standard procedures were used to characterize the prepared NP solids (see Supporting Information).…”
Section: Synthesis and Characterization Of Mesoporous Silica-based Namentioning
confidence: 99%
See 3 more Smart Citations